The brain basis of musicophilia: evidence from frontotemporal lobar degeneration - Fletcher, Phillip D.; Downey, Laura; Witoonpanich, Pirada; Warren, Jason (Frontiers in Psychology, 2013)
Musicophilia, or abnormal craving for music, is a poorly understood phenomenon that has been associated in particular with focal degeneration of the temporal lobes. Here we addressed the brain basis of musicophilia using voxel-based morphometry (VBM) on MR volumetric brain images in a retrospectively ascertained cohort of patients meeting clinical consensus criteria for frontotemporal lobar degeneration: of 37 cases ascertained, 12 had musicophilia and 25 did not exhibit the phenomenon. The syndrome of semantic dementia was relatively over-represented among the musicophilic subgroup. A VBM analysis revealed significantly increased regional grey matter volume in left posterior hippocampus in the musicophilic subgroup relative to the non-musicophilic group (p<0.05 corrected for regional comparisons); at a relaxed significance threshold (P<0.001 uncorrected across the brain volume) musicophilia was associated with additional relative sparing of regional grey matter in other temporal lobe and prefrontal areas and atrophy of grey matter in posterior parietal and orbitofrontal areas. The present findings suggest a candidate brain substrate for musicophilia as a signature of distributed network damage that may reflect a shift of hedonic processing toward more abstract (non-social) stimuli, with some specificity for particular neurodegenerative pathologies.